Political liberalism in Muslim societies - Bilgin, Fevzi (Routledge Islamic studies., 2011)
This book examines Rawls's theory of political liberalism in the context of€Muslim societies, where religion wields a significant social and political influence. Contrasting a sociological analysis with a theoretical approach, the author explores the political questions brought up by religious individuals, organizations, and minorities, and examines fundamental notions such as neutrality of state, public/private distinction, and individual autonomy.